Phenotyping of potato accessions for stable resistance to late blight (Phytophthora infestans) - and VINOD KUMAR, MALKHAN SINGH GURJAR*, SANJEEV SHARMA (Indian Phytopathology, 2016)
Late blight (Phytophthora infestans) is one of the major constraint to potato cultivation in North eastern Himalayan region of India especially in Meghalaya state of India. Forty six exotic accessions along with checks, Indian cultivars like Kufri Giridhari (Highly Resistant), Kufri Himalini (Moderately Resistant) and Kufri Jyoti (Highly Susceptible) were tested for stable resistance in vitro and field conditions (2011 to 2014). Four accessions of potato like CP3605, CP3768, CP3776 and CP3841 (AUDPC=101.5-195.12) were found highly resistant in field conditions but CP3832, CP3839, C3841 showed high resistance in in vitro conditions. Four accessions viz. CP2298, CP3277, CP3766 and CP3774 (AUDPC=230.12- 433.26) were resistant in field whereas in in vitro (detached leaf assay) six accessions viz. CP1839, CP1909, CP2320, CP3364, CP3605, CP3776 were resistant. CP1281, CP1319, CP2187, CP2350, CP2423, CP3765 and CP3787 (AUDPC=331.75-645.75) were found moderately resistant in field. In field testing, seventeen and fourteen potato accessions were found highly susceptible and susceptible respectively whereas only nine accessions were found susceptible in detached leaf assay. In conclusion, seven accessions viz. CP1281, CP2350, CP2423, CP3280, CP3605, CP3776 and CP3841 exhibited highly resistant, resistant, moderately resistant response in laboratory as well as in field conditions. Therefore, these stable resistant accessions can be used for further potato breeding of north eastern Himalayan region of India.